Pengaruh Lingkungan Kerja Fisik Dan Pengawasan Terhadap Kinerja Dengan Kepuasan Kerja Sebagai Variabel Intervening - Salsabila, Aena Jenete; Suwarsono, Bambang; Wahyu K, Brahma (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
This research explains the influence of the physical work environment and supervision on performance with job satisfaction as an intervening variable for non-medical employees at RSUD Dr. Iskak, Tulungagung Regency. The analysis technique in this research uses validity tests, reliability tests, classical assumption tests, partial tests (t tests), and sobel tests. The population in this study was 533 non-medical employees. The sampling technique in this study used nonprobability sampling with the accidental sampling method and the number of samples taken in this study was 85 non-medical employees. In this study, the results showed that the physical work environment had a significant effect on employee performance, supervision had a significant effect on employee performance, the physical work environment had a significant effect on job satisfaction, supervision had a significant effect on job satisfaction, work satisfaction had a significant effect on employee performance, the physical work environment had a significant effect on performance through job satisfaction, supervision has a significant effect on performance through job satisfaction.